Ministerial Decree No. 109/2015 Amending Some Provisions of the Executive Regulation of the Law on Private Insurance Funds = قرار وزاري رقم 109 لسنة 2015 بتعديل بعض أحكام اللائحة التنفيذية لقانون صناديق التأمين الخاصة - Egypt; The middle east library for economic services, translator. (2025)
Ministry of investment decree no. 109 of the year 2015 amending some provisions of the executive regulations of the law on private insurance funds وزارة الاستثمار قرار رقم 109 لسنة 215 بتعديل بعض أحكاماللائحة التنفيذية لقانون صنايق التأمين الخاصة